2018
DOI: 10.1101/328534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysically Realistic Neuron Models for Simulation of Cortical Stimulation

Abstract: 1.AbstractObjectiveWe implemented computational models of human and rat cortical neurons for simulating the neural response to cortical stimulation with electromagnetic fields.ApproachWe adapted model neurons from the library of Blue Brain models to reflect biophysical and geometric properties of both adult rat and human cortical neurons and coupled the model neurons to exogenous electric fields (E-fields). The models included 3D reconstructed axonal and dendritic arbors, experimentally-validated electrophysio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(100 citation statements)
references
References 114 publications
2
98
0
Order By: Relevance
“…Decades of research has shown that neural membranes do respond to high-frequency fields, albeit the dynamics become complex and lead to phenomena, such as conduction block (i.e., inhibition of action potential propagation) (Bhadra et al, 2007(Bhadra et al, , 2019Crosby et al, 2017;Joseph and Butera, 2009;Joseph et al, 2007;Kilgore and Bhadra, 2006;Tai et al, 2005;Zhang et al, 2006aZhang et al, , 2006b. This research has also shown that axons are more susceptible to polarization from (invasive and non-invasive) electric stimulation (Aberra et al, 2018;Chakraborty et al, 2018;Hause, 1975;Howell and McIntyre, 2020;McIntyre et al, 2004;Rahman et al, 2013;Ranck, 1975;Wongsarnpigoon and Grill, 2012). Specifically, ac-tion potentials can be initiated at the axon terminals, in correspondence to maxima of the electric field (Chakraborty et al, 2018;Hause, 1975;Hentall, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research has shown that neural membranes do respond to high-frequency fields, albeit the dynamics become complex and lead to phenomena, such as conduction block (i.e., inhibition of action potential propagation) (Bhadra et al, 2007(Bhadra et al, , 2019Crosby et al, 2017;Joseph and Butera, 2009;Joseph et al, 2007;Kilgore and Bhadra, 2006;Tai et al, 2005;Zhang et al, 2006aZhang et al, , 2006b. This research has also shown that axons are more susceptible to polarization from (invasive and non-invasive) electric stimulation (Aberra et al, 2018;Chakraborty et al, 2018;Hause, 1975;Howell and McIntyre, 2020;McIntyre et al, 2004;Rahman et al, 2013;Ranck, 1975;Wongsarnpigoon and Grill, 2012). Specifically, ac-tion potentials can be initiated at the axon terminals, in correspondence to maxima of the electric field (Chakraborty et al, 2018;Hause, 1975;Hentall, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal models examining membrane properties for different parts of the neuron showed that because dendrites lack myelin (Aberra et al 2018) and have a small diameter (Pashut et al 2011), they respond preferentially to wider pulses (Rattay et al 2012). That was also shown in an animal model experiment were short TMS pulses (~80”s) failed to produce any activation in L5 dendrites (Murphy et al 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Finally, it is to be noted that the electrical properties of each compartment depend on the neuron segments, so the model can be extended to include morphologically detailed neurons for the central nervous system (CNS) (Aberra, Peterchev and Grill, 2018). The model can consist of bifurcations and branches, pre-and post-synaptic terminals, and dendritic arborisation.…”
Section: A Modified Cable Equation Describes the Neuronal Membrane Pomentioning
confidence: 99%